2013
DOI: 10.1001/jamaoto.2013.1744
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Adults

Abstract: Importance: Sensorineural hearing loss is the third leading cause of years lived with disability worldwide. Cochlear implants may provide a viable alternative to hearing aids for this type of hearing loss. The Coverage and Analysis Group at the Centers for Medicare & Medicaid Services was interested in an evaluation of recently published literature on this topic. In addition, this metaanalysis is to our knowledge the first to evaluate qualityof-life (QOL) outcomes in adults with cochlear implants.Objective: To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
112
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(117 citation statements)
references
References 49 publications
3
112
0
2
Order By: Relevance
“…The U.S. Department of Health and Human Services, as indicated in Healthy People 2020, included timely hearing screening with appropriate treatment referral as a priority achievement 1 . The high prevalence of hearing loss has been reported in the literature as well, with over 30 million people age 12 and over experiencing some degree of hearing loss in both ears 2–4 . As the life expectancy in the U.S. continues to climb, the health burden of chronic disease would be expected to increase substantially, making prompt recognition and intervention essential.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The U.S. Department of Health and Human Services, as indicated in Healthy People 2020, included timely hearing screening with appropriate treatment referral as a priority achievement 1 . The high prevalence of hearing loss has been reported in the literature as well, with over 30 million people age 12 and over experiencing some degree of hearing loss in both ears 2–4 . As the life expectancy in the U.S. continues to climb, the health burden of chronic disease would be expected to increase substantially, making prompt recognition and intervention essential.…”
Section: Introductionmentioning
confidence: 96%
“…Sensorineural hearing loss is primarily treated with hearing aids; however, when the degree of loss becomes severe cochlear implantation is the standard of care. In spite of highly rated hearing-related outcomes and quality of life for cochlear implant (CI) patients, 4 this aspect of hearing healthcare is not widely accessed by those who may benefit. Despite an abundance of data to support their efficacy and FDA approval in the United States for 30 years, it is estimated that fewer than 6% of Americans who could benefit from CI have one 5 .…”
Section: Introductionmentioning
confidence: 99%
“…10–12 In one study, 72% of adults diagnosed with a hearing loss reported no desire to pursue hearing aid amplification to treat their hearing loss. 10 Approximately 1.2 millions patients with severe hearing loss are likely candidates for CI with in the US; however, the utilization rate of cochlear implants is only 5%.…”
Section: Introductionmentioning
confidence: 99%
“…This drastically reduces the amount of information that can be extracted from a perceived sound (16,000 channels of information are reduced to 8 channels). Despite this limitation, the cochlear implant remains amongst the most successful neural stimulation systems and can restore speech perception in most subjects [124].…”
Section: Limitations Of Traditional Stimulation Electrodesmentioning
confidence: 99%